Kontroversi HAM dan Budaya - Marsudi Marsudi (Justicia Islamica, 2005)
This study aims to analyze the controversy between human rights and culture, especially in the context of differences in universal values and local wisdom. The method used is qualitative with a descriptive-analytical approach, through a literature review of international human rights documents, cultural theory, and cases that reflect the clash between human rights and local traditions. The results showed that tensions between human rights and culture arise due to differences in perspectives in interpreting individual rights and social norms. On the one hand, human rights emphasize equality and universal freedom, while culture is often based on diverse community values. This study emphasizes that a dialogical and contextual approach is needed to bridge these differences, so that the application of human rights can be aligned with cultural dynamics without neglecting the principles of justice and humanity.